Valsartan Inhibits Angiotensin Ⅱ-induced Proliferation of Vascular Smooth Muscle Cells via Regulating the Expression of Mitofusin 2 - 廖华 龚俊荣 张文娟 郭小梅 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
Angiotensin Ⅱ (ANGⅡ) plays an important role in the pathogenesis of atherosclerosis by inducing proliferation of vascular smooth muscle cells (VSMCs).In our study,we observed the effects of valsartan on proliferation of cultured VSMCs treated with or without ANGⅡ by cell counting and methyl thiazolyl tetrazolium (MTT) assay,and detected the expression of mitofusin 2 (Mfn2),a newly discovered cell proliferation inhibitor and a related cell proliferation signaling pathway pro-tein by Western blotting.ANGⅡ at a concentration of 10-6 mol/L significantly stimulated VSMCs proliferation,down-regulated the expression of Mfn2 and upregulated the expression of Raf and ERK1/2.Valsartan inhibited such effects of ANGⅡ at concentrations of 10-5 and 10-6 mol/L,but not at 10-7 mol/L.Valsartan had no significant effect on the proliferation of untreated VSMCs.These results suggest that valsartan inhibits ANGⅡ-induced proliferation of VSMCs in vitro via Mfn2-Ras-Raf-ERK/MAPK signaling pathway.